Stabilization of the lower hybrid instability excited by longitudinal currents in multi-ion plasma - Venugopal, C.; Kurian, M.J.; Antony, S.; Kumar, C.P. Anil; Renuka, G. (My University, 2006)
We have investigated the stability of the lower hybrid wave in a plasma containing hydrogen and positively and negatively charged oxygen ions. The electrons, streaming parallel to the magnetic field, can excite the instability provided their drift velocity exceeds the parallel phase velocity of the wave. This is true for both the collisionless and collisional cases. The growth/damping rate is modified by a factor dependent directly on the number densities and square of the charges on the oxygen ions and inversely on the masses of these ions. Thus oxygen ions, irrespective of the nature of the charge on them, tend to stabilize the wave; the higher the degree of ionization of the oxygen ions, the greater the stabilization for a given number density.
Keywords: Oxygen ions; Magnetic field; Multi-ion plasma; Lower hybrid instability